Resolving the psyllid tree of life: phylogenomic analyses of the superfamily Psylloidea (Hemiptera). (20th April 2018) - Percy, Diana M.; Crampton‐Platt, Alex; Sveinsson, Saemundur; Lemmon, Alan R.; Lemmon, Emily Moriarty; Ouvrard, David; Burckhardt, Daniel
Abstract: Understanding evolutionary relationships in the superfamily Psylloidea is challenging due to the lack of clear morphological synapomorphies for many groups. Some families and many of the genera, including the two largest, Cacopsylla Ossiannilsson and Trioza Foerster, have long been acknowledged as nonmonophyletic and the circumscription of natural groups has remained fluid. We present the best phylogenetic hypothesis to date for Psylloidea and provide a working systematic framework to better reflect evolutionary relationships. A shotgun sequencing approach using mixed pool DNAs for more than 400 species resulted in recovery from de novo assemblies of near‐complete mitogenomes (≥10 kb) for 359 species, and partial genomes (5–10 kb) for an additional 40 species. The resulting phylogeny improves and clarifies the family classification and resolves some of the longstanding uncertainties in relationships within and between genera. A whole‐nuclear‐genome scan approach (yielding data from an estimated 373 nuclear genes) using the anchored hybrid enrichment method for a representative subset of taxa confirms the placement of major groupings and overall tree topology recovered with the mitochondrial data. The data generated represent a major increase in molecular resources for this superfamily. In addition, we highlight areas of remaining uncertainty that require further sampling and/or additional sources of data. The phylogeny provides new insights for both evolutionary and applied research, and a backbone constraint tree allows the placement of taxa of particular interest or concern (e.g. pest taxa) with only small fragments of sequence available (e.g. DNA barcodes). Abstract : A new phylogenomic framework is provided for the superfamily Psylloidea. Comprehensive sampling (> 400 species across all families) and data from mitochondrial (complete or near‐complete mitogenomes for 359 species) and nuclear gene regions greatly enhance genetic resources available for Psylloidea. Our analysis clarifies and confirms the circumscription of natural groups and provides a psyllid tree of life with which to interpret evolutionary processes at multiple scales.